Readings that shelter, voices that welcome. Implementation of a reading workshop with children from the community of Sacsamarca within the framework of the University Social Responsibility (USR) - Sandoval Figueroa, Carmen María (2021)
In 2019, a teacher and a group of students from a teacher training program at a private university in Lima designed a reading workshop aimed at children from the rural community of Sacsamarca (Ayacucho) whose ages ranged from 3 to 12 years. The objectives of the workshop were to create a space for shared reading so that children have access to the book outside of the school context and to implement a home loan system for books to promote the circulation of books. The workshop was part of the “Como Jugando” project, with a focus on university social responsibility and had a duration of 12 sessions (2 per month) between June and December. The reading workshop was a permanent proposal, coexisting with other educational proposals such as outdoor play, creative art, music, psychomotor skills, among others. The workshop’s methodological support was the approach of reading mediation. The design of the workshops, as well as their execution, were in charge of the students. The reading proposals were diverse, responding to the interests and proposals of the children. Finally, this experience has shown children interested in reading and appropriation of content, motivating interactions between readers at reading out loud and conversation moments.